Technical Specification of Extension-Connection for Axial Tension C-Section Cold-Formed Steel (CFS) - Muhammad Alif Irwan Rusnan; Ahmad Fahmy Kamarudin; Seyed Jamalaldin Seyed Hakim; Sharifah Salwa Mohd Zuki; Ade Faisal; Mohamad Dtauwel (International Journal of Integrated Engineering, 2025)
Cold-Formed Steel (CFS) structures are increasingly used in construction due to their light weight, cost-effectiveness, and ease of fabrication. However, limitations in design standards for CFS connections hinder further structural optimization. This study examines the tensile performance of four C-section connection types Face-to-Face Web (FTF-W), Face-to-Face Flange (FTF-F), Back-to-Back (BTB), and Sleeve Flange (SF) subjected to axial tension. A total of 48 samples were tested using two CFS thicknesses (0.75mm and 1.00mm) and two screw configurations (2 and 4 number of screws), in accordance with AISI S100 (2016) and ASTM E8 (2022). Analytical resistances were calculated based on Eurocode 3 (2006), covering net tension, bearing, and shear. BTB connections consistently demonstrated the best performance, with experimental-to-design resistance ratios exceeding 1.0 across most failure modes. At 0.75mm thickness with four screws, BTB’s bearing resistance exceeded design estimates by over 135%. In contrast, FTF-W showed the weakest performance, with a net tension ratio as low as 0.12 approximately 87% lower than BTB due to eccentric loading and poor screw engagement. Increasing material thickness improved net tension ratios by 20–50% in stronger configurations (BTB, FTF-F, SF), while adding more screws enhanced tensile strength but often reduced shear resistance by 20–25% due to over-constraint. Failure modes included bearing deformation, screw tilting, and snapping, each influenced by geometry and fastener configuration. The findings highlight BTB’s structural reliability and emphasize the need for improved design in FTF-W connections.